1999
DOI: 10.1023/a:1021932009936
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purposes of this study were (a) to estimate the prevalence of Attention-Deficit/Hyperactivity Disorder (AD/HD) symptoms in the general preschool and school population; and (b) to analyze the influence of gender, age, and socioeconomic status (SES) variables on AD/HD symptoms. Out of the 80,000 preschool and schoolchildren living in Manizales, Colombia, a random sample of 540 children was selected. Two gender, three age (4- to 5-year olds, 6- to 11-year olds, and 12- to 17-year olds), and three SES (low, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(19 citation statements)
references
References 27 publications
3
14
0
2
Order By: Relevance
“…In the Spanish context, our estimates of prevalence of ADHD in children aged 3–6 years (5.4%) are similar to those reported by a previous study [ 20 ]. Studies in 4 and 5 years-old children from Colombia (6.2% to 18.2%) [ 21 , 37 ] and Japan (7.0%) [ 22 ] showed also similar or higher prevalence of probable ADHD symptoms than ours (7.2%). Moreover, in 6 years-old children, Spanish and international studies reported higher rates of probable ADHD symptoms than ours (2.5%).…”
Section: Discussionsupporting
confidence: 74%
“…In the Spanish context, our estimates of prevalence of ADHD in children aged 3–6 years (5.4%) are similar to those reported by a previous study [ 20 ]. Studies in 4 and 5 years-old children from Colombia (6.2% to 18.2%) [ 21 , 37 ] and Japan (7.0%) [ 22 ] showed also similar or higher prevalence of probable ADHD symptoms than ours (7.2%). Moreover, in 6 years-old children, Spanish and international studies reported higher rates of probable ADHD symptoms than ours (2.5%).…”
Section: Discussionsupporting
confidence: 74%
“…Prevalence of ADHD was found to be highest among children in the age group of 10 -11 years in our study which is validated by several studies showing that children with a mean age of 9 -11 years were the most affected by ADHD [14,15,16,17]. ADHD is more prevalent among the male children compared to female [3,11,18], which is proven in our study as well.…”
Section: Discussionsupporting
confidence: 89%
“…The absence of found significant difference for the sorts is concordant with works found in specific literature 17 18 6 8 19 . On the other hand, research demonstrates performance of the feminine sort better when compared with masculine 20 21 22 23 24 , fact this explained due to bigger difficulty to diagnosis children of the feminine sort for the attentional deficit, for present less exacerbated behaviors of what the masculine sort 25 . Research refer 26 that the ability of auditory attention of women is better because they obtain to keep it, exactly for a stimulation without meaning as the noise.…”
Section: Discussionmentioning
confidence: 99%